2006
DOI: 10.1016/j.jcrs.2006.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the straylight effects of cataracts

Abstract: The BPM 2 filter is a good early-cataract-simulating filter. Stacking such filters is a good way to increase the cataract density. A drawback is that the BPM 2 filter has a transmission of 66% so stacking filters reduces the overall transmission significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
98
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(106 citation statements)
references
References 19 publications
6
98
0
2
Order By: Relevance
“…They differ in the particle number, and consequently, in the scattering effect. It has been shown that straylight-angular dependence of the BPM filters agrees well with that of the human eye [18].…”
Section: Validation Testmentioning
confidence: 58%
“…They differ in the particle number, and consequently, in the scattering effect. It has been shown that straylight-angular dependence of the BPM filters agrees well with that of the human eye [18].…”
Section: Validation Testmentioning
confidence: 58%
“…The amount of retinal stray light is different for each individual and in the young, normal eye is roughly caused onethird by the cornea (increased by corneal dystrophies), 83 one-third by the lens (increased by cataracts), 84,85 and one-third by the iris, sclera and fundus (sensitive to changes in pigmentation and vitreous turbidity). 86 The stray light naturally increases with age due to increasing media opacification.…”
Section: Retinal Stray Lightmentioning
confidence: 99%
“…The increased opalescence of the lens with cataract development results in increased forward light scatter [21] that produces a veiling Abstract Purpose: The CVA is an interactive, automated computer device that rapidly thresholds central acuity under conditions mimicking customary photopic and mesopic activities. In sequence, the CVA may test up to 6 environments, in this series under 3 mesopic environments (98%, 50% MC against 1.6 cd/m 2 background, 25% MC against 5 cd/m 2 ), then 3 glare environments (98%, 10% and 8% MC, against 200 cd/m 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, whereas the pupil diameter of a healthy 20-year-old on average is 5.3 mm in dim illumination, the pupil of a 60-year-old typically has a diameter of 3.2 mm [20] resulting in one third of the retinal illumination in dim environments. Contrast sensitivity testing has been demonstrated to remain stable until the age of approximately 65 years beyond which it and overall visual function decline rapidly [12,19], thought primarily due to senile miosis and progressive nuclear sclerosis, as well as with the aging of neural elements, both retinal and brain [20].The increased opalescence of the lens with cataract development results in increased forward light scatter [21] that produces a veiling Abstract Purpose: The CVA is an interactive, automated computer device that rapidly thresholds central acuity under conditions mimicking customary photopic and mesopic activities. In sequence, the CVA may test up to 6 environments, in this series under 3 mesopic environments (98%, 50% MC against 1.6 cd/m 2 background, 25% MC against 5 cd/m 2 ), then 3 glare environments (98%, 10% and 8% MC, against 200 cd/m 2 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation